Transient Arrest of Germinal Vesicle Breakdown Improved In Vitro Development Potential of Buffalo (Bubalus Bubalis) Oocytes. Issue 1 (19th June 2017) - Kumar, Sandeep; Kumar, Manish; Dholpuria, Sunny; Sarwalia, Parul; Batra, Vipul; De, Sachinandan; Kumar, Rakesh; Datta, Tirtha Kumar
ABSTRACT: Germinal vesicle breakdown (GVBD) is the first milestone that an oocyte needs to achieve toward completing the maturation and gaining potential to fertilize. Significantly lower in vitro embryo production rate in buffaloes can be attributed to heterogeneity of GVBD occurrence among oocytes obtained from abattoir derived ovaries. Evidence from our earlier work had suggested that different qualities of buffalo oocytes differ significantly in their timing of GVBD. Besides, these oocytes also differ in terms of volume of Akt phosphorylation, which initiates the process of GVBD. With objective of synchronizing the oocytes for GVBD, immature buffalo oocytes were subjected to a two‐step culture protocol, initially in the presence of GVBD inhibitors and subsequently, in vitro maturation (IVM) with added SC79 (activates Akt). Expression of developmentally important genes was assessed along with embryo development rate and blastocyst health to interpret the consequences. Oocytes subjected to a short GVBD inhibition period of 6 h followed by IVM with SC79 resulted in improved cleavage and blastocyst rates. Resultant blastocysts also possessed higher ICM: TE ratio. Further, GVBD inhibited oocytes displayed a sustained cytoplasmic maturation status in terms of reorganization of cortical granules (CGs), mitochondrial membrane potential, and glutathione levels during the period of inhibition. We conclude that a temporary GVBD arrest of buffalo oocytes and modulation of Akt improves the in vitro embryo development rate as well as quality of resultant embryos. Besides, our meiotic arrest protocol does not affect the cytoplasmic maturation. J. Cell. Biochem. 119: 278–289, 2018. © 2017 Wiley Periodicals, Inc. Abstract : A short meiotic arrest using combination of inhibitors followed by in vitro maturation in presence of Akt activator synchronizes buffalo oocytes for improved future development competence. Our GVBD inhibition protocol and culture conditions could be of potential use in techniques requiring temporary meiotic hold as pre‐requisite.